2022
DOI: 10.1039/d2nr02118h
|View full text |Cite
|
Sign up to set email alerts
|

An assembly-inducing PDC enabling the efficient nuclear delivery of nucleic acid for cancer stem-like cell suppression

Abstract: Nucleic acid therapy is attracting great attention in diverse clinical translations because of its therapeutic advantages. As a renowned oligonucleotide therapeutical candidate in clinical stage, AS1411 has shown outstanding tumor...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Wang et al reported the use of a 5-FU conjugated peptide (FU-NHOH(19), Scheme 7) for the delivery of nucleic acid into nucleus of cells. [22] in addition to 5-FU, 19 contains a hydroxamic acid group at the C-terminus to inhibit histone deacetylases (HDACs). The authors used 19 to coassemble with an anticancer aptamer, AS1411, which is a 26-mer guanine-rich oligonucleotide DNA in phase II clinical trials for relapsed or refractory acute myeloid leukemia and renal cell carcinoma.…”
Section: Peptides Conjugated With Anticancer Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al reported the use of a 5-FU conjugated peptide (FU-NHOH(19), Scheme 7) for the delivery of nucleic acid into nucleus of cells. [22] in addition to 5-FU, 19 contains a hydroxamic acid group at the C-terminus to inhibit histone deacetylases (HDACs). The authors used 19 to coassemble with an anticancer aptamer, AS1411, which is a 26-mer guanine-rich oligonucleotide DNA in phase II clinical trials for relapsed or refractory acute myeloid leukemia and renal cell carcinoma.…”
Section: Peptides Conjugated With Anticancer Drugsmentioning
confidence: 99%
“…Wang et al. reported the use of a 5‐FU conjugated peptide (FU‐NHOH( 19 ), Scheme 7) for the delivery of nucleic acid into nucleus of cells [22] . in addition to 5‐FU, 19 contains a hydroxamic acid group at the C‐terminus to inhibit histone deacetylases (HDACs).…”
Section: Assemblies Of the Conjugates Of Peptide And Drugmentioning
confidence: 99%